Autogenous bone combined with anorganic bovine bone for maxillary sinus augmentation: Analysis of the osteogenic potential of cells derived from the donor and the grafted sites - de Melo, Willian M.; de Oliveira, Fabiola S.; Marcantonio, Élcio; Beloti, Marcio M.; De Oliveira, Paulo T.; Rosa, Adalberto L. (Wiley, 2013)
Objectives: This study aimed to comparatively evaluate the in vitro osteogenic potential of cells obtained from the mandibular ramus (MR, autogenous bone donor site) and from the maxillary sinus (MS) bone grafted with a mixture of anorganic bovine bone (ABB) and MR prior to titanium implant placement (MS, grafted implant site). Material and methods: Cells were obtained from three patients subjected to MS floor augmentation with a 1: 1 mixture of ABB (GenOx Inorg®) and MR. At the time of the sinus lift procedure and after 8 months, prior to implant placement, bone fragments were taken from MR and MS, respectively, and subjected to trypsin-collagenase digestion for primary cell culturing. Subcultured cells were grown under osteogenic condition for up to 21 days and assayed for proliferation/viability, osteoblast marker mRNA levels, alkaline phosphatase (ALP) activity and calcium content/Alizarin red staining. ALP activity was also determined in primary explant cultures exposed to GenOx Inorg® (1: 1 with MR) for 7 days. Data were compared using either the Mann-Whitney U-test or the Kruskal-Wallis test. Results: MS cultures exhibited a significantly lower osteogenic potential compared with MR cultures, with a progressive increase in cell proliferation together with a decrease in osteoblast markers, reduced ALP activity and calcium content. Exposure of MR-derived primary cultures to GenOx Inorg® inhibited ALP activity. Conclusion: These results suggest that the use of GenOx Inorg® in combination with MR fragments for MS floor augmentation inhibits the osteoblast cell differentiation at the implant site in the long term. © 2013 John Wiley & Sons A/S.
Keywords: Anorganic bovine bone; Autogenous bone; Bone grafts; Cell culture; Gene expression; Maxillary sinus augmentation; Osteoblast